2020
DOI: 10.1162/glep_a_00547
|View full text |Cite
|
Sign up to set email alerts
|

Political Perspectives on Geoengineering: Navigating Problem Definition and Institutional Fit

Abstract: Geoengineering technologies are by definition only effective at scale, and so international policy development of some sort will be unavoidable. It is therefore important to include governability as a dimension when assessing the technologies’ feasibility and potential role in addressing climate change. The few existing studies that address this question indicate that for some technologies, policy development at the international level could be exceedingly difficult. This study provides an in-depth, theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…This research has demonstrated how discussions on the feasibility and responsibility of various CE approaches have prioritized scientific and technical knowledge types Barben, 2018, 2020;Low and Schäfer, 2020). This is seen as particularly problematic in the Global South, where memories of broken promises mean that NETs may be seen as means for the Global North to avoid their responsibilities to reduce emissions (Cox et al, 2020a;Möller, 2020). Although the heterogeneous range of CE proposals raise differing governance challenges, a bounded range of expert knowledges have been shown to have both direct de facto governance effects on how the various techniques are being researched and developed, and indirect effects on how de jure governance (policy) is emerging (Boettcher, 2019;Gupta and Möller, 2019).…”
Section: The Role Of Discoursementioning
confidence: 96%
See 1 more Smart Citation
“…This research has demonstrated how discussions on the feasibility and responsibility of various CE approaches have prioritized scientific and technical knowledge types Barben, 2018, 2020;Low and Schäfer, 2020). This is seen as particularly problematic in the Global South, where memories of broken promises mean that NETs may be seen as means for the Global North to avoid their responsibilities to reduce emissions (Cox et al, 2020a;Möller, 2020). Although the heterogeneous range of CE proposals raise differing governance challenges, a bounded range of expert knowledges have been shown to have both direct de facto governance effects on how the various techniques are being researched and developed, and indirect effects on how de jure governance (policy) is emerging (Boettcher, 2019;Gupta and Möller, 2019).…”
Section: The Role Of Discoursementioning
confidence: 96%
“…A wider body of research on CE assesses how different types of discourse may be shaping the development of technology governance (Harnisch et al, 2015;Biermann and Möller, 2019;Boettcher, 2019;Low and Boettcher, 2020;Möller, 2020). This research has demonstrated how discussions on the feasibility and responsibility of various CE approaches have prioritized scientific and technical knowledge types Barben, 2018, 2020;Low and Schäfer, 2020).…”
Section: The Role Of Discoursementioning
confidence: 99%
“…Finally, we expect the main focus on CDR in the strategies and interviews to be on approaches that are not strictly considered to be climate engineering (CE) approaches (e.g., managing the Earth's radiation uptake). While CE methods have entered academic and popular science debates (Caldeira, 2009;Huttunen and Hildén, 2014;Himmelsbach, 2018;Lefale and Anderson, 2018;Low and Schäfer, 2019), alongside or interchangeably with CDR (Bellamy, 2013;Sapinski et al, 2020), and have been in focus in multilateral negotiations broadly aimed at limiting deployment (Bodansky, 2013;Möller, 2020;McLaren and Corry, 2021), solar radiation management is not yet a significant part of domestic policy debates (Reynolds, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Second, most actors currently discussing solar geoengineering are natural scientists, climate modelers and social scientists writing about governance; policy makers are only beginning to be involved [ 85 ]. Yet such expert visions are important, since they have the power to de facto shape the future governance and policy landscape for solar geoengineering [ 86 ].…”
Section: Discussionmentioning
confidence: 99%